Peran Dukungan Suami dan Bidan selama Kehamilan dalam Penentuan Metode Kontrasepsi Pasca Persalinan pada Masa Pandemi Covid-19 - Deviati Juwita Sari; Dwi Izzati; Andriyanti Andriyanti (JURNAL KEBIDANAN BESTARI, 2022)
Background: Continuity of care in obstetrics is a series of continuous and comprehensive service activities ranging from pregnancy, childbirth, puerperium, newborn services and family planning services The attitude and support of the husband can be a reinforcement and encouragement for the wife in using contraception tools. Midwives are a great place to discuss and provide contraception. The use of postpartum contraceptives has been shown to be higher when contraceptive counseling is administered over the antenatal and postpartum time periods. Methods: This research is a descriptive study with a case study starting from March 2021-April 2022. Case Report: Telehealth assistance is carried out 2-4 times / month from 13-14 weeks of gestation. Postpartum contraceptive counseling is administered from 28 weeks gestational age. The companion provides counseling regarding the types of contraceptive methods along with their advantages and side effects, then the mother is advised to discuss with the husband the contraceptive plan chosen for use after childbirth. Mothers and husbands choose this steady contraceptive method because it is enough to have only 2 children and the husband considers the age of the mother which if pregnant again can cause a high risk for the mother. Conclusion: Continuity of care is the right opportunity for midwives to be able to provide continuous and quality care and provide counseling that is in accordance with the needs of mothers since hami, childbirth, puerperium and babies, even during the Covid-19 pandemic, especially postpartum counseling contraceptive during pregnancy. Husband support and the role of midwives have an influence on the use of postpartum contraceptives, so there is a need for support from husbands and midwives in carrying out a joint commitment to the use of postpartum contrception in the antenatal period. Keywords : Husband support, midwife role, contraception, postpartum